Diverse Effects of Amino Acids on Monascus Pigments Biosynthesis in Monascus purpureus - Yin, Sheng; Zhu, Yiying; Zhang, Bin; Huang, Baozhu; Jia, Ru (Frontiers in Microbiology, 2022)
Amino acids could act as nitrogen sources, amido group donors, or bioactive molecules in fungi fermentation, and consequently, play important roles in Monascus pigments (MPs) biosynthesis. But the understanding of the effects of various amino acids on MPs biosynthesis is still incomprehensive. In this work, 20 free amino acids were added to the fermentation medium to evaluate their effects on MPs biosynthesis in Monascus purpureus RP2. Six amino acids, namely, histidine (HIS), lysine (LYS), tyrosine (TYR), phenylalanine (PHE), methionine (MET), and cysteine (CYS), were selected as the valuable ones as they exerted significant effects on the production yield and even on the biosynthesis metabolic curves of MPs. Moreover, the dose-dependent and synergistic effects of valuable amino acids on MPs biosynthesis were observed by tests of serial concentrations and different combinations. In addition, it revealed that HIS and MET were the prominent amino acids with dominant and universal influences on MPs biosynthesis. The analog compounds of HIS (amitrole) and MET [calcium 2-hydroxy-4-(methylthio)] were added to the fermentation medium, and the results further confirmed the extraordinary effects of HIS and MET and their analogs on MPs biosynthesis. Furthermore, the gene transcription profile indicated that a differential expression pattern was observed in the polyketide synthase (PKS) cluster responsible for MPs biosynthesis in response to HIS and MET, revealing that they could oppositely regulate MPs biosynthesis in different ways. These findings would benefit the understanding of MPs biosynthesis regulation mechanism in M. purpureus and contribute to the industrial production of MPs by fermentation.